The Socio-Affective Principle of Language Learning vis-a-vis Speaking Proficiency of English Major Students - Abrera, Evangeline M.; Umbao, Eloisa Jean C.; Belmonte, Maria Alleah N.; Roldan, Jessica; Lasala, Abegail V.; Mirate, Teodoro Jan M.; Ocampo, Darrel M. (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aimed to evaluate the extent of awareness of socio-affective principles of language learning and the speaking proficiency level of English major students of Central Bicol State University of Agriculture – Sipocot. This descriptive-correlational research utilized survey questionnaires and the impromptu and extemporaneous speeches to gather the data from the respondents. Results showed that respondents were highly aware about the socio-affective domain of language learning (overall mean of 3.32); proficient along extemporaneous speech (19.52 total average); and proficient along impromptu speech (20.88 total average). Moreover, there is no significant difference in the extent of awareness of the respondents across year level about the socio-affective domain of language learning (0.966 F-value and 0.388 p-value); and there is a significant difference in the speaking proficiency across year level (5.783 F-value and 0.006 p-value). Lastly, it was revealed that there is a significant relationship between the extent of awareness of the respondents about the socio-affective domain of language learning and their speaking proficiency level (r-value of 0.329 and a p-value of 0.017). The researchers recommended that continuous language exposure must still be given importance. Additionally, the active participation of the learners, language teachers, and the school community is pivotal in the language learning of the learners. Multifarious activities inside of the school such as English organization, theatre and debate club, workshops, and school broadcasting club are also recommended.